THE “GRAY ZONES” OF MAPUCHE HISTORIES. INTERNALIZED COLONIALISM, MARGINALITY AND POLITICS OF MEMORY - Nahuelpán Moreno, Héctor (Revista de Historia Social y de las Mentalidades, 2014)
The “gray zones” of Mapuche histories can be understood as everyday spaces in which complex social and intersubjectives interactions develop as part of experiences of social suffering, ways of survival, resilience, and resistance performed by Mapuche men and women under conditions of social marginality and colonial violence. These spaces, interactions and experiencies are constitutive of family histories, of the heterogeneous and contradictory Mapuche identity, but they are subalternized within Mapuche official historical, indigenist and nationalist narratives. This article discusses the idea of “gray zones” of Mapuche histories as an interpellation to inter-weave experiencies and remembrances, in order to deal with the dispersion and fragmentation of memories that make possible the reproduction of colonialism as a mode of hegemony and culture.